2022
DOI: 10.1038/s41556-022-00998-6
|View full text |Cite
|
Sign up to set email alerts
|

Intron-encoded cistronic transcripts for minimally invasive monitoring of coding and non-coding RNAs

Abstract: Despite their fundamental role in assessing (patho)physiological cell states, conventional gene reporters can follow gene expression but leave scars on the proteins or substantially alter the mature messenger RNA. Multi-time-point measurements of non-coding RNAs are currently impossible without modifying their nucleotide sequence, which can alter their native function, half-life and localization. Thus, we developed the intron-encoded scarless programmable extranuclear cistronic transcript (INSPECT) as a minima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…At 48 h after transfection, cells were selected for 2 weeks with 0.5 μg ml −1 puromycin dihydrochloride (Gibco, Thermo Fisher Scientific) in the presence of 0.5 μM AZD7648 (MedChemExpress, catalog no. HY-111783) (a DNA-PKcs inhibitor 32 ) and a CAG-promoter-driven i53 (a 53BP1 inhibitor) to inhibit NHEJ and shift the DNA repair towards HDR 33,34 . The surviving polyclonal population carrying the eTLR system stably in the AAVS1 locus was monoclonalized using limiting dilution in 96-well plates.…”
Section: Articlementioning
confidence: 99%
“…At 48 h after transfection, cells were selected for 2 weeks with 0.5 μg ml −1 puromycin dihydrochloride (Gibco, Thermo Fisher Scientific) in the presence of 0.5 μM AZD7648 (MedChemExpress, catalog no. HY-111783) (a DNA-PKcs inhibitor 32 ) and a CAG-promoter-driven i53 (a 53BP1 inhibitor) to inhibit NHEJ and shift the DNA repair towards HDR 33,34 . The surviving polyclonal population carrying the eTLR system stably in the AAVS1 locus was monoclonalized using limiting dilution in 96-well plates.…”
Section: Articlementioning
confidence: 99%
“…Paraspeckles cannot be formed or maintained upon loss of NEAT1 [7][8][9] . Although NEAT1 is primarily located in the nucleus and plays important regulatory roles, studies have shown that NEAT1 is also localized in the cytoplasm 10 . As a long non-coding RNA (lncRNA), NEAT1 acts as a competitive endogenous RNA (ceRNA) in the cytoplasm, exerting sponge-like effects by interacting with microRNA molecules and regulating their activity and availability [11][12][13][14] .…”
Section: Introductionmentioning
confidence: 99%